The Problem of Misconceptions about Guidance and Counseling Globally - Rahmi Dwi Febriani; Triyono Triyono; Puji Gusri Handayani; Triave Nuzila Zahri; Azmatul Khairiah Sari (Universitas PGRI SUMATERA BARAT, 2024)
Counseling is a service provided by professional staff to individuals or groups for the development of effective daily living. However, the phenomenon that occurs in the field is that the implementation of Guidance and Counseling in schools is carried out with an unclear pattern, the lack of clarity on the pattern that must be implemented has an impact on the bad image of guidance and counseling, giving rise to misconceptions about the implementation of counseling guidance. The emergence of negative perceptions regarding the implementation of Guidance Counseling, various criticisms emerged as a form of disappointment with the counselor's performance, resulting in misunderstandings. Misconceptions are defined as understandings that conflict with the concepts put forward by experts. So, the aim of the research is to describe the problem of misconceptions about guidance and counseling. This type of research is a literature study. by searching, studying and analyzing theoretical references relevant to the problems found. The literature review method is a series of activities related to library data collection methods, reading and recording and managing research materials. Other problems that often cause misconceptions about counseling guidance in schools are: (1) counseling guidance teachers are often seen as school police, (2) counseling guidance is often thought of as a medium for giving advice, (3) counseling guidance is thought to only deal with cases of problematic students. , (4) guidance and counseling teachers must be more active in dealing with student problems, and (5) the profession as a guidance and counseling teacher can be done by anyone